From understanding a simple DC motor to developing an electric vehicle AI controller rapid prototype using MATLAB-Simulink, real-time simulation and complex thinking - Ponce, Pedro; Ramirez, Ricardo; Ramirez, Maria Soledad; Molina, Arturo; MacCleery, Brian; Ascanio, Mack (Frontiers in Education, 2022)
Traditional undergraduate courses that only cover theoretical aspects and do not allow students to interact and produce practical results through experimentation are insufficient today. The students are not exposed to educational innovation, so they can have difficulties when they need to propose something original. On the other hand, conventional theoretical and laboratory courses in which students follow specific directions for achieving predefined goals do not allow students to create novel solutions and integrate the innovation process as a standard methodology. Moreover, beginning in 2020, the COVID-19 pandemic forced professors to implement digital tools and materials to continue education intensively. This proposed course presents an alternative to promote practical and theoretical knowledge in students. Besides, engineering students must create innovative solutions to increase the quality of life in rural and urban communities, which calls for novel experimental approaches. Electric drives are fundamental elements in electric systems and industrial processes proposed to save energy or control electric machines. In addition, industries urge specialized engineers who can tackle complex industrial problems. The proposed educational methodology can be implemented in manufacturing, agriculture, robotics, and aerospace problems, among many others. Hence, low-cost devices to validate the proposed solutions became used by students to achieve novel solutions using electric drives. This paper describes an undergraduate course called "Digital Control of Electric Machines" (electric drives) and its implementation of the Tec-21 Educational Model of Tecnologico de Monterrey, V Model, MATLAB/Simulink, low-cost hardware, and complex thinking. The content of the course begins with electric machine models and power electronics that allow students to move from the basic to the advanced industrial electric drive problems in a friendly manner. In addition, the V-model and Modelo Tec 21 are used as fundamental pillars of the leading innovative structure of the proposed course. The results showed that students mastered several soft and hard skills to accomplish complex design goals, including controlling an electric rapid prototype vehicle.